Circulation of shelf waters in the KwaZulu-Natal Bight, South Africa. (1st June 2016) - Roberts, MJ; Nieuwenhuys, C; Guastella, LA
Abstract : Ship-based acoustic Doppler current profiler (S-ADCP) technology, used in survey mode, has enabled near- synoptic views of the in situ 3-D current field in the KwaZulu-Natal (KZN) Bight to be elucidated for the first time. Data acquired by the research vessels RS Africana and RS Algoa in June 2005, September 2007, March 2009 and July 2010 are presented. Each S-ADCP dataset showed similar circulation characteristics whereby the continental slope and outer shelf of the KZN Bight were strongly influenced by the south-westward flowing Agulhas Current. This was particularly evident in the extreme north between Cape St Lucia and Richards Bay where the shelf is narrowest and velocities exceeded 200 cm s−1. The widening of the bight to the south moves the Agulhas Current further from the coast, resulting in a diminishing velocity gradient on the outer shelf which terminates around the midshelf axis. The southern region of the bight was mostly influenced by the Durban cyclonic eddy (Durban Eddy), and in June 2005 and September 2007, by a cyclonic 'swirl' that occupied the entire southern half of the KZN Bight, the latter identified by a combination of S-ADCP-, satellite-derived SST- and ocean colour data. Satellite data showed low-chlorophyll offshore water to move into this swirl and northwards along the inner- and midshelf, reaching the Thukela River. Inner-shelf circulation north of the Thukela River was weak (<20 cm s−1) and highly variable. Satellite-tracked surface drogues deployed in the Durban Eddy found their way into the northward coastal current in the KZN Bight, with velocities exceeding 90 cm s−1 at times. The drogues also highlighted the strong influence of wind, especially in the northern bight between Durnford Point and Cape St Lucia, with residence times on the shelf exceeding 14 days, suggesting this region to be of biological importance particularly for recruitment.